2022
DOI: 10.1155/2022/6201067
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Artificial Intelligence in Discovery and Development of Anticancer and Antidiabetic Therapeutic Agents

Abstract: Spectacular developments in molecular and cellular biology have led to important discoveries in cancer research. Despite cancer is one of the major causes of morbidity and mortality globally, diabetes is one of the most leading sources of group of disorders. Artificial intelligence (AI) has been considered the fourth industrial revolution machine. The most major hurdles in drug discovery and development are the time and expenditures required to sustain the drug research pipeline. Large amounts of data can be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 169 publications
(168 reference statements)
0
2
0
1
Order By: Relevance
“…Segundo, os indivíduos registraram em tempo real em um aplicativo de smartphone atividades relacionadas à ingestão de alimentos, práticas de exercícios e sono. Outros estudos, igualmente baseados em técnicas de IA, têm demonstrado sucesso no contexto da medicina de precisão voltado para doenças crônicas como neoplasias malignas [96], hipertensão [97] e diabetes [98]. Neste contexto, os sistemas de IA são promissores para aprofundar os conhecimentos da fisiopatologia das doenças.…”
Section: Serviços Inteligentes Baseados Em Aprendizado De Máquinaunclassified
“…Segundo, os indivíduos registraram em tempo real em um aplicativo de smartphone atividades relacionadas à ingestão de alimentos, práticas de exercícios e sono. Outros estudos, igualmente baseados em técnicas de IA, têm demonstrado sucesso no contexto da medicina de precisão voltado para doenças crônicas como neoplasias malignas [96], hipertensão [97] e diabetes [98]. Neste contexto, os sistemas de IA são promissores para aprofundar os conhecimentos da fisiopatologia das doenças.…”
Section: Serviços Inteligentes Baseados Em Aprendizado De Máquinaunclassified
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%